2021
DOI: 10.3389/fpls.2021.661542
|View full text |Cite
|
Sign up to set email alerts
|

Combined Spraying of Boron and Zinc During Fruit Set and Premature Stage Improves Yield and Fruit Quality of European Hazelnut cv. Tonda di Giffoni

Abstract: Boron (B) and zinc (Zn) are essential micronutrients of plant nutrition programs in orchards for securing the crop quality and yield. Although orchard supplementation with B and Zn is a common practice to overcome deficiencies or maintain their optimal levels, the efficiency of combined B and Zn spraying in relation to European hazelnut (Corylus avellana L.) phenological stage has not been investigated so far. Leaf and kernel mineral and functional traits were studied in cultivar Tonda di Giffoni after B and Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…In fruit species, B and Zn are important elements for normal fruit growth and development, whose deficiency affects metabolic processes, such as reduced shoot growth, mineral and nutritional alteration, and fruit quality ( Marschner, 2012 ; Özenç and Özenç, 2015 ; Davarpanah et al., 2016 ). Foliar application of B and Zn in different doses in European hazelnut ( Corylus avellana ) show that only Zn significantly increases in kernels, and also leads to rises in Ca and Na concentration in leaves ( Meriño-Gergichevich et al., 2021 ). The authors conclude that the foliar application of B and Zn (at 800 and 400 mg L -1 respectively) are the most efficient doses for boosting the yield of fruits per plant.…”
Section: Interaction Of B and Microelementsmentioning
confidence: 99%
“…In fruit species, B and Zn are important elements for normal fruit growth and development, whose deficiency affects metabolic processes, such as reduced shoot growth, mineral and nutritional alteration, and fruit quality ( Marschner, 2012 ; Özenç and Özenç, 2015 ; Davarpanah et al., 2016 ). Foliar application of B and Zn in different doses in European hazelnut ( Corylus avellana ) show that only Zn significantly increases in kernels, and also leads to rises in Ca and Na concentration in leaves ( Meriño-Gergichevich et al., 2021 ). The authors conclude that the foliar application of B and Zn (at 800 and 400 mg L -1 respectively) are the most efficient doses for boosting the yield of fruits per plant.…”
Section: Interaction Of B and Microelementsmentioning
confidence: 99%
“…Therefore, both byproducts exhibit large hardness and toughness [5,6]. In relation to hazelnut shell thickness of around 1.75 mm [9,20], walnut shell thickness ranges between 1.1 to 1.7 mm according to reports by Koyuncu et al [43] (Table 2).…”
Section: Mass Yield and Morphological Featuresmentioning
confidence: 94%
“…Chile has become the main producer country from the Southern Hemisphere, with an off-season nut supply of approximately 52,100 t (4.73% of total world production) in the 2021/2022 season [18] and an estimated production of 136,000 t year −1 for 2030 [18,19]. This nutshell has a mass value of over 50% of the total fruit weight (w/w) in stabilized nut [9,20]. It is becoming the main hazelnut byproduct production.…”
Section: Productive Context and Expectative Of Hazelnut And Walnut Sh...mentioning
confidence: 99%
“…Guilherme et al's findings indicated that appropriate levels of boron can regulate plasma membrane H-ATPase activity and enhance nutrient absorption in citrus trees, thereby increasing citrus yields [36]. Meriño-Gergichevich et al stated that boron and zinc supplementation may enhance the uptake of macronutrients, thus leading to enhanced yield [37]. Along with these lines of evidence, numerous studies have demonstrated that applying boron and zinc micro-fertilizers can effectively boost crop yields; however, determining the optimal application dose remains crucial for achieving maximum productivity gains.…”
Section: Yieldmentioning
confidence: 99%